Analysis of Personal Hygiene Status and Basic Sanitation with the Incidence of Stunting in Toddler (case study of Pantai Labu Sub-District) - Annisa Rizka Lestari; Sri Malem Indirawati; Nurmaini Nurmaini (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
The second sustainable development goal, which aims to achieve food security and eradicate hunger and all kinds of malnutrition by 2030, includes stunting as one of its priorities. WASH and personal hygiene are indirect risk factors for stunting, if environmental sanitation and personal hygiene are poor, it can increase the risk of stunting in toddlers. The purpose of this study was to determine the effect of personal hygiene status and basic sanitation on the incidence of stunting in Pantai Labu sub-district. The research was conducted from August to October 2023 in five villages that have been determined to be the locus of stunting in the district, namely Paluh Sibaji, Regemuk, Denai Kuala, Bagan Serdang, and Sei Tuan Villages. This research method uses a case control design population in this study were mothers of toddlers who were stunted in Pantai Labu District, totaling 55 toddlers. Sample taken by total sampling with a total of 55 stunted toddlers and 55 toddlers who were not stunted and a total sample of 110 toddlers. This research uses primary and secondary data, with data collection using questionnaires and observation sheets. Data analysis using logistic regression test presenting with odds ratio (OR) and 95% confidence interval (95% CI) by using SPSS version 25. The results showed that personal hygiene of toddlers (OR = 4.259; 95% CI 1.749-10.372; p = 0.001), personal hygiene of mothers (OR = 4.571; 95% CI 1.752-11.928; p=0.002), and ownership of latrines (OR=2.260; 95% CI 1.051-4.859; p=0.037) influenced the incidence of stunting in Pantai Labu sub-district. Access to drinking water, waste water disposal facilities, and waste disposal facilities had no effect on the incidence of stunting (p>0.05). Mothers are advised to improve personal hygiene for both mothers and toddlers and always fulfill the criteria for latrines to meet the requirements. Keywords: Stunting, Personal hygiene, Sanitation